"Start to stop": results of a randomised controlled trial of a smoking cessation programme for teens. (26th November 2003) - Robinson, L A; Vander Weg, M W; Riedel, B W; Klesges, R C; McLain-Allen, B
Abstract : Objective: To examine the feasibility, acceptability, and effectiveness of a school based smoking cessation programme among students caught smoking at school. Design: A randomised controlled trial comparing cessation rates among students in a behavioural cessation programme and those receiving self help materials only. Setting: Eighteen schools in the Memphis, Tennessee area. Subjects: Two hundred and sixty one adolescent cigarette smokers (166 male, 95 female) averaging 15.8 years of age. Intervention: Students assigned to the intervention received a four session behavioural treatment programme administered individually by a health educator. In addition, these students received stage matched intervention in brief phone calls monthly until the one year follow up. Main outcome measure: Self reported and biochemically verified smoking cessation at post-test and 12 month follow up. Results: Recruiting students who were caught smoking at school proved to be highly successful. Participants rated the programme favourably, and retention rates were high. Although treated participants improved more in tobacco related knowledge relative to controls (p  =  0.002), there were no group differences in changes in attitudes toward smoking. In addition, treated and control participants demonstrated no significant differences in cessation rates both at post-test and follow up. Comparisons between self reported cessation rates and those obtained under bogus pipeline conditions or with biochemical verification suggested significant falsification of cessation among participants. Conclusions: Our results failed to demonstrate any significant effect of the cessation programme on smoking rates for treated adolescents compared with controls. Our findings also highlight the importance of utilising strong methodology in research on adolescent smoking cessation, including control groups and biochemical verification of smoking status.